All Days 2010
DOI: 10.2118/135107-ms
|View full text |Cite
|
Sign up to set email alerts
|

Profile Modification in Injection Wells Through Relative Permeability Modifiers: Laboratory Validation and Reservoir Simulation

Abstract: Waterflooding is a well-established technique in the oil industry to improve hydrocarbon recovery in a given reservoir. However, in the absence of profile modification, water injected into the reservoir will go into the high-permeability zones and will bypass the oil-saturated, low-permeability zones. This paper presents the laboratory validation and reservoir simulation of a relative permeability modifier (RPM) used for profile-modification improvement in injection wells. By injecting the RPM within the high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Chemical solutions like sealants, RPM (relative permeability modifiers), and water-swellable polymers at both injectors and producers simultaneously can selectively modify the wettability behavior of high permeable zones (Vasquez and Miranda 2010) and allow injectant fluids to move into the un-swept low permeability hydrocarbon zones. Conformance solutions have been successfully used with the spectrum of EOR technologies.…”
Section: Mature Fields Key Processes and Technologiesmentioning
confidence: 99%
“…Chemical solutions like sealants, RPM (relative permeability modifiers), and water-swellable polymers at both injectors and producers simultaneously can selectively modify the wettability behavior of high permeable zones (Vasquez and Miranda 2010) and allow injectant fluids to move into the un-swept low permeability hydrocarbon zones. Conformance solutions have been successfully used with the spectrum of EOR technologies.…”
Section: Mature Fields Key Processes and Technologiesmentioning
confidence: 99%
“…14. Additionally, offset producers observed an increase in oil production and a water cut decrease a few months after the RPM treatment (Vasquez and Miranda, 2010). …”
Section: Case History 13 (West Africa)mentioning
confidence: 99%
“…The sealing polymer gel could, in principle, act as a porosity filler material that completely blocks pores of reservoir rock and stops fluids from flowing . In contrast, RPM is a polymer or weak polymer gel that adsorbs onto the surface of pore spaces and/or rents in pore throats. RPMs are capable of selectively reducing relative permeability to water with little or no effect on oil flow. The RPM selective blocking mechanisms on fluid phases are still a matter of debate. Many researchers have indicated that a wall effect, as shown in Figure.…”
Section: Introductionmentioning
confidence: 99%